The Influence of Socioeconomic Factors on Postharvest Losses of Fish in Small-scale Fisheries in East Java Province - Amelia, Balqis Salma; Sari, Dyah Wulan (Universitas Islam Lamongan, 2025)
This study aims to analyze the influence of environment, experience, education, temperature, work hour, age, fishermen group, access internet, and government aid on post-harvest fish losses. The sample of this study was taken from Banyuwangi district consisting of Muncar and Blimbingsari sub-districts, and Lamongan district consisting of Paciran and Lamongan sub-districts. This study uses a quantitative approach and regression estimation using Ordinary Least Square (OLS), to see the influence between the independent variables on the dependent variables in the study. The results of this study show that the variables of environment, education, experience, and fishermen group have a significant influence on post-harvest fish loss. In addition, the highest post-harvest fish loss (PHFL) was found in Blimbingsari sub-district, Banyuwangi district. Another location with a high PHFL value was Muncar sub-district. In contrast, Paciran and Brondong sub-districts in Lamongan district had lower PHFL values. The findings have managerial and academic implications. For policy makers and fisheries organizations, the results of this study highlight the need to increase access to efficient storage technologies and provide training to improve fishers' skills in post-harvest handling. Academically, this study contributes to the fisheries economics literature by offering empirical evidence on the key factors affecting PHFL in small-scale fisheries. There are still gaps in integrated empirical studies and in policies that address human resources and institutional support. Therefore, this study provides important insights for designing more holistic and targeted strategies to reduce PHFL in East Java.